Extension of G-Algebras to SuperHyper G-Algebras - Marzieh Rahmati; Mohammad Hamidi (Neutrosophic Sets and Systems, 2023)
The theory of superhyperalgebras is a new concept in the study of all branches of algebra structures. In this paper, we introduce a novel concept of (m, n)-superhyper G-algebra and present several results from the study of certain properties of (m, n)-superhyper G-algebras. The purpose of this paper is the study an extension of G-algebras to (m, n)-superhyper G-algebras, as a generalization of a logic algebra. The main motivation of this work was obtained based on an extension of G-algebra to superhyper G-algebra based on the n th-power set of a set.